DEVELOPMENT OF DISTANCE EDUCATION IN UKRAINE - Лаврухіна, Тетяна Василівна (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2016)
The article deals with the concept of «distance education». Indices of assessing the quality of the implementation and application of distance learning. Formed priority measures on introduction of distance learning in higher education. Highlight the negative side, approaches problems and prospects of distance learning